Secure Mindmetrics Authentication Mechanism with Log Files. (2016) - Sebastian, Jerrin; Madhu, Arun; Job, Deepu
Abstract: Security is inevitable feature of any web application. Most of the web applications have some kind of design or developmental fault which can be easily exploited by hackers. These faults help them to gain illegal access to the system. Hence majority of attacks are focused on applications thereby stealing user's sensitive data and information.Authentication is an important factor of securityin computing system. Usually login ID's are used for identification and passwords are used for verification. Other mechanisms like secondary or graphical passwords, One time password, Challenge response, Biometric login, Behavioral pattern and Location based authentication can be used.But implementation of these mechanisms requires specialized devices which are not reliable. This paper deals with an enhanced version of Mindmetric authentication mechanism, which grants access only to valid users and helps the admin to determine malicious users with the help of logfiles. It can also be used for preventing users from various attacks. It can augment the current password based system by strengthening the identification process.Mindmetrics system raises security of authentication system over single or double password systems. Even If password is hacked, login attempts by attackers will be blocked by the identification server. It is very simple, scalable and does not require any specialized devices or complex algorithms.